Aspectos epidemiológicos e terapêuticos da enteropatia proliferativa suína. - Silvia de Araujo Franca (2007)
This dissertation comprises three experiments. The first one, evaluated the house sparrow susceptibility to L. intracellularis experimental infection. Only two sparrows had discrete antigen labelling in the lamina propria and all fecal samples were negative by PCR. Thus, it seems that house sparrows are not important in the epidemiology of PPE. Another two studies were conducted to evaluate the efficacy of leucomycin and acetyl-isovaleryl-tylosin (AIVT) for the prevention and control of PPE. Ninety healthy five week-old pigs were balanced by weight and then randomly allotted to three groups, with 30 pigs per treatment. In the study with leucomycin, the groups were: T1, no medication/challenged; T2, 90 ppm of leucomycin/challenged; T3, 180 ppm of leucomycin/challenged. All animals were challenged with L. intracellularis organisms. Clinical presentation of the disease was more evident in T1 than in T2, T3 animals. T2 and T3 animals had higher ADG (0.419g and 0.438g vs. 0.339g) and better FC (1,63 and 1,44 vs. 1,83) than T1. In the study with AIVT, the groups were: T1, no medication/challenged; T2, 50 ppm of AIVT /challenged; T3, 100 ppm of tiamulin/challenged. Clinical presentation of the disease was more evident in T1 than in T2 and T3. T2 and T3 animals had higher ADG (0.541g and 0.568g vs. 0.451g) and better FC (1,58 and 1,59 vs. 1,84) than T1. Average lesion length in T1, T2 and T3 was 94.9, 6.1 and 6.8 cm, respectively. The reproduction of the disease was successful. The efficacy of leucomycin, at the doses of 90 and 180 ppm, and of AIVT at the dose of 50 ppm, was demonstrated.Keywords: pigs; house sparrow; proliferative enteropathy; Lawsonia intracellularis; epidemiology, antimicrobials; control.